Role of vitamin D supplementation as adjunctive therapy to escitalopram in patients of major depressive disorder: a 8 week prospective, randomized, interventional, clinical study - Singh, Shivangna; Sharma, Priyamvada; Gautam, Vivek (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Depression is a major public health problem and occurs in persons of all ages, and is associated with increased morbidity, soaring costs for treatment and reduced productivity and quality of life. Vitamin D is involved in numerous brain processes including neuroimmunomodulation, neuroprotection, neuroplasticity, regulation of neurotrophic factors, and making it biologically plausible to be associated with depression. Aim of the present study is to compare the therapeutic effects of vitamin D given along with escitalopram versus escitalopram given alone in patients with major depressive disorder. Methods: In this prospective, randomized, interventional clinical study, 60 patients with a diagnosis of major depressive disorder based on ICD-10 criteria were randomly assigned into two groups, one group received 60000IU vitamin D3 weekly plus 10 mg escitalopram OD daily while the other group received escitalopram10 mg OD daily alone for 8 weeks. Depression severity was assessed at 2-week intervals using the 24-item Hamilton Depression Rating Scale (HDRS). Serum 25(OH) vitamin D levels were measured in all the patients at baseline and after intervention. Result: Fifty nine patients completed the trial. Depression severity based on HDRS decreased significantly after intervention, with a significant difference between the two groups. The vitamin D3+escitalopram combination was significantly better than escitalopram alone from the fourth week of treatment. Conclusion: Role of vitamin D in mood disorder and its dietary supplementation is effective as an adjuvant treatment along with SSRIs in depressive disorders, especially in vitamin D deficient patients.